Indigenous research methodologies and listening the Dadirri way - LJ Waller (2018)
Researchers who want to undertake projects that amplify First Nations perspectives face a range of complex methodological and ethical considerations. This chapter explores how some of these challenges can be addressed by working with Indigenous epistemologies. Dadirri is the language of the Ngangikurungkurr people of Northern Australia and also a foundational concept that involves deep listening and underpins how they live, act, understand and feel. Engoori is a set of diplomatic protocols for resolving conflict that belong to the Mithaka people of south-west Queensland. The chapter concludes that working with Indigenous knowledge can not only shift ways of seeing and hearing, but the collaborations we form, the questions we ask, the findings we make and the actions that flow from this.